Measuring romantic attachment in Spanish adolescents: Validation of the brief form of the Experiences in Close Relationships-Revised (ECR-R) questionnaire - Fernández Fuertes, Andrés A.; Orgaz, Begoña; Fuertes, Antonio; Carcedo, Rodrigo (Anales de Psicología / Annals of Psychology, 2011)
This work deals with the development and validation of the brief version of the Experiences in Close Relationships–Revised (ECR-R) Questionnaire for adolescents. The sample was selected using a cluster sampling, considering the classrooms of the different schools of Salamanca as sampling units or clusters. Finally, a total of 598 adolescents (35.8% males and 64.2% females) participated in this study. The main result found was that the original version of ECR-R of 36 items was reduced to 18, presenting appropriate levels of adjustment indexes and reliability for the anxiety and avoidance subscales. In addition, the correlation found between the latent factors was very low. In summary, the short-form of the ECR-R adapted to Spanish population and proposed in this study, has shown to be useful to evaluate and measure romantic attachment in adolescents.